2020
DOI: 10.3389/fnagi.2020.603179
|View full text |Cite|
|
Sign up to set email alerts
|

A 5-min Cognitive Task With Deep Learning Accurately Detects Early Alzheimer's Disease

Abstract: Introduction: The goal of this study was to investigate and compare the classification performance of machine learning with behavioral data from standard neuropsychological tests, a cognitive task, or both.Methods: A neuropsychological battery and a simple 5-min cognitive task were administered to eight individuals with mild cognitive impairment (MCI), eight individuals with mild Alzheimer's disease (AD), and 41 demographically match controls (CN). A fully connected multilayer perceptron (MLP) network and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 86 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…CI and MCI were classified with 81% and 96.6% of accuracy with recurrent neural networks (RNN) and artificial neural networks (ANN), respectively [ 43 , 62 ]. A study using multi-layer perceptrons (MLP) with cognitive data showed that 92.98% of AD cases were accurately diagnosed [ 63 ]. The mini-mental state examination (MMSE) and clinical dementia ratio (CDR) tests were also used to further classify AD stages with ResNet and DenseNet, which resulted in 99% accuracy [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CI and MCI were classified with 81% and 96.6% of accuracy with recurrent neural networks (RNN) and artificial neural networks (ANN), respectively [ 43 , 62 ]. A study using multi-layer perceptrons (MLP) with cognitive data showed that 92.98% of AD cases were accurately diagnosed [ 63 ]. The mini-mental state examination (MMSE) and clinical dementia ratio (CDR) tests were also used to further classify AD stages with ResNet and DenseNet, which resulted in 99% accuracy [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…ML models were employed by G. Lee et al [ 62 ], without mentioning any particular algorithm’s name, and showed 88% accuracy. Using multilayer perceptron (MLP) modeling, AD classification with 92.98% of accuracy was achieved [ 63 ]. In [ 40 ], the authors developed a model using the decision tree classifier with hyperparameter tuning (DTC-HPT) and observed high accuracy of 99% for identifying AD.…”
Section: Discussionmentioning
confidence: 99%
“…MLP model is a feed-forward artificial neural network (ANN) model that is applicable to a non-linear inseparable issue; Almubark et al demonstrated the predictive value of this approach in their previous study ( 26 ). The generalization and efficacy of this method have been widely confirmed in several papers ( 27 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, eye-movement measurements come in as a relatively low-cost measurable indicator (biomarker) of one’s homeostatic (mental) state. It has been reported that cognitive dysfunctions detected through gaze analysis may indicate or even predict mental disease processes ( Fujioka et al, 2016 ; Almubark et al, 2020 ; Wolf et al, 2021 ). Moreover, studies of significant importance have produced preliminary findings that show that gaze-metrics parameters such as fixations (their location, number and duration), saccades (their number and amplitudes) and the scan-path length, are abnormal in a great number of neurological diseases ( Beedie et al, 2011 ; Benson et al, 2012 ; Türkan et al, 2016 ; Li et al, 2020b ; Morita et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%